A phosphoinositide‐specific phospholipase C pathway elicits stress‐induced Ca2+ signals and confers salt tolerance to rice. Issue 3 (3rd February 2017) - Li, Li; Wang, Fawei; Yan, Peiwen; Jing, Wen; Zhang, Chunxia; Kudla, Jörg; Zhang, Wenhua
Summary: In animal cells, phospholipase C (PLC) isoforms predominantly hydrolyze phosphatidylinositol‐4, 5‐biphosphates [PtdIns(4, 5)P2 ] into the second messengers diacylglycerol (DAG) and inositol 1, 4, 5‐trisphosphate [Ins(1, 4, 5)P3 ] to regulate diverse biological processes. By contrast, the molecular mechanisms and physiological significance of PLC signaling in plants still awaits full elucidation. Here, we identified a rice ( Oryza sativa cv) PI‐PLC, OsPLC1, which preferred to hydrolyze phosphatidylinositol‐4‐phosphate (PtdIns4P) and elicited stress‐induced Ca 2+ signals regulating salt tolerance. Analysis by ion chromatography revealed that the concentration of PtdIns4P was c . 28 times of that of PtdIns(4, 5)P2 in shoots. OsPLC1 not only converted PtdIns(4, 5)P2 but also – and even more efficiently – converted PtdIns4P into DAG and Ins(1, 4, 5)P3 in vitro and in vivo . Salt stress induced the recruitment of OsPLC1 from cytoplasm to plasma membrane, where it hydrolyzed PtdIns4P. The stress‐induced Ca 2+ signaling was dependent on OsPLC1, and the PLC‐mediated Ca 2+ signaling was essential for controlling Na + accumulation in leaf blades, thus establishing whole plant salt tolerance. Our work identifies a conversion pathway and physiological function for PtdIns4P pools in rice and reveals the connection between phosphoinositides and Ca 2+ signals mediated by PLC during salt stress responses.